慶祝林樂培八十大壽—聖樂合唱作品音樂會 = Concerto das Obras Corais Sacras em Honra do 80.º Aniversário de Doming Lam - Coro Perosi; Vanessa Leão, Maria; Ng, João (Coro Perosi, 2004)
printed in macau

English grammar for students of Latin: the study guide for those learning Latin - Goldman, Norma (Olivia and Hill Press, 2004)
Study guide for students of Latin. Explains grammatical terms in Latin and shows how they relate to English grammar. Review exercises with answers. Suitable for self-study, and developing grammar skills
OCLC: 57073642
Keywords: English language Grammar; Comparative Latin; Latin language Grammar; Comparative English; Latin language materials

牛津高階英漢雙解詞典, 第六版, 英漢雙解版 = Oxford advanced learner's English-Chinese dictionary, 6th ed. - Hornby, Albert Sydney; Wehmeier, Sally (Oxford University Press, 2004)
OCLC: 1293885968
Keywords: 1900-1999; Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language–Dictionaries–Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English; English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language–Dictionaries–English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; English language; 英語 20 世紀 字典; 英語 20 世紀 字典 漢語; 英語 字典

靈頌 (時節篇) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2004)